Microbial Exopolymers: Sources, Chemico-Physiological Properties, and Ecosystem Effects in the Marine Environment - Andreas Teske (Frontiers Research Topics, 2018)
Microorganisms (bacteria, archaea, microeukaryotes) in marine environments secrete a diverse array of exopolymeric substances that facilitate attachment to surfaces, the formation of organic colloids and larger aggregations of cells (marine snow), and that can influence many ocean, as well as global, processes. The aim of this Research Topic is to highlight recent advances in the sources, chemistry and function of these microbial-produced macromolecules. We encouraged original research and reviews on exopolymeric substances, from their sources, chemico-physiological properties, functions and ecosystem effects, and including their role in the Gulf of Mexico following the Deepwater Horizon oil spill disaster.